A Bootstrap Structure Directly Charged by BUS Voltage with Threshold-Based Digital Control for High-Speed Buck Converter - Yujie Guo (MDPI AG, 2021)
This article proposes a high-frequency, area-efficient high-side bootstrap circuit with threshold-based digital control (TBDC) that is directly charged by BUS voltage (DCBV). In the circuit, the voltage of the bootstrap is directly obtained from the BUS voltage instead of the on-chip low dropout regulator (LDO), which is more suitable for a high operating frequency. An area-efficient threshold-based digital control structure is used to detect the bootstrap voltage, thereby effectively preventing bootstrap under-voltage or over-voltage that may result in insufficient driving capability, increased loss, or breakdown of the power device. The design and implementation of the circuit are based on CSMC 0.25 µm 60 V BCD technology, with an overall chip area of 1.4 × 1.3 mm2, of which the bootstrap area is 0.149 mm2 and the figure-of-merit (FOM) is 0.074. The experimental results suggest that the bootstrap circuit can normally operate at 5 MHz with a maximum buck converter efficiency of 83.6%. This work plays a vital role in promoting the development of a wide range of new products and new technologies, such as integrated power supplies, new energy vehicles, and data storage centers.